TRANSLATION ANALYSIS OF PROMISING AND OFFERING UTTERANCES IN FORREST GUMP MOVIE - Dwianasari, Anita (Journal of Language and Literature, 2018)
The purpose of the paper is to analyze the promising and offering utterances in commissive of speech act, translation techniques and its equivalences in Forrest Gump movie subtitles. The method used is qualitative method. The results showed several techniques employed, such as adaptation, borrowing, established equivalent, linguistic compression, literal translation, modulation, particularization, reduction, transposition, and variation. The translation technique mostly used is established equivalence. For the shift rendering in source text and target text in Forrest Gump movie subtitles, it is concluded that mostly the data do not occur any shift in promising or offering utterances. Also, in terms of translation equivalence, the dominant kind of translation equivalence in this research is dynamic equivalence.